Broadening Our Field of View: The Role of Emotion Polyregulation. (July 2019) - Ford, Brett Q.; Gross, James J.; Gruber, June
The field of emotion regulation has developed rapidly, and a number of emotion regulatory strategies have been identified. To date, empirical attention has focused on contrasting specific regulation strategies to determine their unique profile of consequences. However, it is becoming clear that people commonly pursue multiple regulation approaches within any given emotional episode (e.g., pursuing different regulation goals, strategies, or tactics). We refer to the concurrent or sequential use of multiple approaches to regulate emotions within a single emotion episode as polyregulation. Here, we extend existing theoretical frameworks of emotion regulation to consider polyregulation. We then pose several core questions to summarize and inspire research on polyregulation, thereby improving our understanding of emotion regulation as it unfolds in everyday life.